Design and Manufacture of Air Pressure Measuring Instruments With Arduino Microcontroller-Based Presure Water Sensors - Ahmad Ismail Shaleh; Alexius Ulan Bani; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
Air pressure measuring instrument with arduino microcontroller-based air pressure sensor uses c++ programming language. This research aims to be used by the general public to determine the air pressure on vehicle tires and provide early warning of air pressure conditions in tires, because many people who use motor vehicles often experience problems or accidents due to air pressure that is not in accordance with safety standards. Mpx5700AP sensor circuit connected to arduino uno, required a call library that serves to add program functions displaying characters on mpx5700AP. Then the MPX5700AP sensor is given air pressure by entering air through a straw or hose. After the air enters, the arduino will process and will be displayed by the LCD. If the air pressure exceeds 120kPa, the arduino activates the Buzzer.